Aprendizagem baseada em projetos em aulas de Física : conceitos relacionados a acidentes de trânsito - Aguillera, Andreia Gomes Furtado (2021)
The present study had as its general objective to evaluate a proposal for teaching Physics in the context of traffic accidents, based on the active methodology "Project Based Learning" (PBL) and as specific objectives: to elaborate a didactic proposal; analyze the proposal with the students; the applicator teacher; school and workshop teachers. The instruments for data collection were: articles, dissertations, theses, questionnaires, structured interviews and Webquest. In the first moment, an analysis was made of the works that have been developed about PBL, in contexts of Physics teaching. The results indicated a variety of theoretical and methodological assumptions related to the PBL methodology, as well as the concern of the authors in providing a more engaging learning to the students, which is related to real situations present in everyday life, seeking more meaningful learning. Factors have also been identified that can hinder the implementation of PBL proposals if they are not taken into account. The didactic proposal was applied, in a partial way, by a Physics teacher to the students of the 1st year of High School of the Escola Estadual Ulisses Guimarães, in the city of Campo Verde - MT. From a context of Emergency Remote Teaching, in which not all the proposal was possible to be applied, signs of learning were still identified through the Webquests answered by the students, corrected from the evaluation rubric. The rubric proved to be an effective learning assessment tool, as it tends to be more objective, decreasing the subjectivity of the grade. The applying professor considers that the proposal is possible to be applied in the state school system due to the need for little investment and the interest aroused in the students. Still in order to meet the foreseen objectives, an online workshop entitled: PPGECN - I Virtual Day of Physics Teaching - Workshops from Statics to Dynamics was made to demonstrate the proposal to Basic Education teachers. On the occasion, thirty (30) teachers participated. After analyzing the applied questionnaire, it was found that the vast majority already knew the PBL methodology, but only 40% said they had already worked with the methodology in the classroom. The proposal was approved by the teachers, corroborating the relevance of the suggested theme and its relationship with the students' daily lives. The final version of the educational product “Project-Based Learning: Concepts related to traffic accidents” will be made available to the academic community, through the repository of the Master's Program in the Teaching of Natural Sciences at the Federal University of Mato Grosso.